Reliability of Electronic versus Attendance Examination among Undergraduate Medical Students In Covid-19 Era - Amenah Fadhil Ridha; Zainab Abdul Ameer Jaafar; Wassan Nori (AlQalam Journal of Medical and Applied Sciences, 2024)
COVID-19 raised a rapid progressing health problem. Iraq has taken drastic steps to combat the pandemic, including suspending all in-person educational activities. The consequent integration of e-learning into universities has issued student evaluation challenges. Electronic exams were implemented to evaluate medical college students.: A cross sectional study reviewed recorded marks of 275 fourth grade medical students in the Department of Obstetrics and Gynecology/ Mustansiriyha University in the form of a single best answer. In addition, their means were compared with the standards of the same students in three electronic exams that were performed at the time of the health ban.Analysis showed a mean mark for the attendance exam was 70.54±24.8 versus 91.51±17.35out of 100 marks for the electronic exam. The rate of achieving high grades in E exams was 79.3% versus 20.4% of students in electronic exams. The success rate in the electronic exam was 95.6%, whereas in the attendance exam, 82.9%.In view of the present health crisis, including integral E-learning and implementing attendance examinations may be the best possible choice. Still, the unacceptably high success rates with high-grade scales in electronic exams necessitate accurate assessment models to avoid this negative consequence. أثار كوفيد - 19 مشكلة صحية سريعة التطور. اتخذ العراق خطوات جذرية لمكافحة الوباء، بما في ذلك تعليق جميع الأنشطة التعليمية الشخصية. وقد أدى التكامل الناتج عن التعلم الإلكتروني في الجامعات إلى ظهور تحديات في تقييم الطلاب. تم تنفيذ الاختبارات الإلكترونية لتقييم طلاب كلية الطب. قامت دراسة مقطعية بمراجعة الدرجات المسجلة لـ 275 طالب طب في الصف الرابع في قسم أمراض النساء والتوليد الجامعة المستنصرية في شكل أفضل إجابة واحدة. بالإضافة إلى ذلك، تمت مقارنة متوسطاتهم مع معايير نفس الطلاب في ثلاثة اختبارات إلكترونية تم إجراؤها وقت الحظر الصحي. وأظهر التحليل أن متوسط علامة الامتحان الحضوري كان 24.870.54 مقابل 17.3591.51 من أصل 100 درجة للامتحان الإلكتروني. وبلغت نسبة تحقيق درجات عالية في الامتحانات الإلكترونية 79.3% مقابل %20.4 للطلبة في الامتحانات الإلكترونية. وبلغت نسبة النجاح في الامتحان الإلكتروني %95.6%، بينما في الامتحان الحضوري 82.9% في ضوء الأزمة الصحية الحالية، قد يكون تضمين التعلم الإلكتروني المتكامل وتنفيذ اختبارات الحضور هو أفضل خيار ممكن. ومع ذلك، فإن معدلات النجاح المرتفعة بشكل غير مقبول مع المقاييس العالية في الامتحانات الإلكترونية تتطلب نماذج تقييم دقيقة لتجنب هذه النتيجة السلبية